Ethnic Conflict in the Western World - Esman, Milton J. (Cornell University Press, 2019)
Why, in the late 1960's, did ethnic minorities such as Scots and Welsh, Quebecois, Bretons and Basques unexpectedly begin to protest and assert their demands with fresh vigor, confidence, and even violence? What are the factors that help to explain the activation of these ethnic political movements, some of which now threaten the continued integrity of such long-established states as Canada and Great Britain? This book represents the first systematic attempt to deal with the re-emergence of ethnic conflict in Western societies. In addition to three historical and theoretical essays, there are eleven case studies of countries where ethnic nationalism has become politically significant. In a concluding chapter the editor comments on the theoretical and policy implications of the country studies.